Revealing antimicrobial resistance profile of the novel probiotic candidate Faecalibacterium prausnitzii DSM 17677 - Machado, Daniela (2022)
Faecalibacterium prausnitzii, a resident anaerobic bacterium commonly found in healthy gut microbiota, has been proposed as a next generation probiotic with high potential for application in food matrices and pharmaceutical formulations. Despite its recognized health benefits, detailed information regarding its antimicrobial susceptibility profile is still lacking. However, this information is crucial to determine its safety, since the absence of acquired antimicrobial resistance is required to qualify a probiotic candidate as safe for human and animal consumption. Herein, the antimicrobial susceptibility profile of F. prausnitzii DSM 17677 strain was evaluated by integrating both phenotypic and in silico data. Phenotypic antimicrobial susceptibility was evaluated by determining minimum inhibitory concentrations of 9 antimicrobials using broth microdilution and E-test® methods. Also, the whole genome of F. prausnitzii DSM 17677 was analysed, using several databases and bioinformatics tools, to identify possible antibiotic resistance genes (ARG), genomic islands (GI) and mobile genetic elements (MGE). With exception of erythromycin, the same classification (susceptible or resistant) was obtained in both broth microdilution and E-test® methods. Phenotypic resistance to ampicillin, gentamycin, kanamycin and streptomycin were detected, which was supported by the genomic context. Other ARG were also identified but they seem not to be expressed under the tested conditions. F. prausnitzii DSM 17677 genome contains 24 annotated genes putatively involved in resistance against the following classes of antimicrobials: aminoglycosides (such as gentamycin, kanamycin and streptomycin), macrolides (such as erythromycin), tetracyclines and lincosamides. The presence of putative ARG conferring resistance to β-lactams could only be detected using a broader homology search. The majority of these genes are not encoded within GI or MGE and no plasmids were reported for this strain. Despite the fact that most genes are related with general resistance mechanisms, a streptomycin-specific ARG poses the only potential concern identified. This specific ARG is encoded within a GI and a MGE, meaning that it could have been laterally acquired and might be transferred to other bacteria present in the same environment. Thus, our findings provide relevant insights regarding the phenotypic and genotypic antimicrobial resistance profiles of the probiotic candidate F. prausnitzii DSM 17677.